Pengaruh Kinerja Lingkungan, Good Corporate Governanace, dan Ukuran Perusahaan Terhadap Pengungkapan SDGs Pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2022-2024 - Zaschia Flanivolya Matulessy; Tries Ellia Sandari (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Thiss study analysess thee influencee off environmentall performance,e Good Corporate Governance, and company ssize onn SDG disclosuree in mining ccompanies llisted oon tthe Indonesia sStock Exchangefor the period 2022–2024, both partially and simultaneously. Of the 101 companies, 31 wwere selectedd ass sampless using gpurposive ssampling. Dataa analysiss wass conductedd using SPSS. The resultss indicatee thatt onlyy companyy size has a significant partial effect, while Good Corporate Governance andd environmentall  performancee do not have an effect. However, the three variables together havee assignificant eeffect oon SDGs disclosure.